HUBUNGAN ANTARA TINGKAT KEPATUHAN PERAWAT TERHADAP SOP (STANDAR OPERASIONAL PROSEDUR) PERAWATAN LUKA DENGAN PROSES PENYEMBUHAN LUKA PASIEN PASCABEDAH DI RSUD dr. H. ANDI ABDURRAHMAN NOOR - Farhandika Putra, Muhammad Suhada (AKPER Pemkab Purworejo, 2021)
SOP is a procedure or stage that is standardized and must be passed to complete a particular work process and is part of the nurses' skills in applying their knowledge. Injuries are a break in the continuity of a tissue caused by an injury or surgical process. The wound healing process is influenced by several factors, one of which is wound management such as wound care. The aim of this study was to determine the correlation between the level of nurse obedience to SOP (Standard Operational Procedure) wound care with the wound healing process after surgery. This type of study was a correlation with using cross sectional design. The samples in this study were 20 nurses and 20 patients by using purposive sampling technique. This study was conducted in the RSUD dr. H. Andi Abdurrahman Noor Kabupaten Tanah Bumbu. The results of study indicated that the level of nurse obedience in the very obedient category was (40%) and the results of observations in the wound healing process were (55%) at the level of the category that was not good. After statistical tests by using the Spearman Rank test obtained P value of 0.032 <(0.05). The conclusion of this study, that there was correlation between the level of nurse obedience to SOP (Standard Operational Procedure) wound care with wound healing process after surgery. Obedience, Nurse, Wound Healing Process, SOP (Standard Operational Procedure) wound care, After Surgery.